Amount of Proteinuria and Duration of Expectant Management in Severe Preeclampsia - Cozzi, Gabriella D.; Battarbee, Ashley N.; Sanjanwala, Aalok R.; Casey, Brian M.; Subramaniam, Akila (American Journal of Perinatology, 2022)
Objective The aim of the study is to evaluate the association between the amount of proteinuria at the time of diagnosis of preeclampsia with severe features (severe preeclampsia [SPE]) and duration of expectant management (EM) and other perinatal outcomes.Study Design This is a retrospective cohort study of patients with SPE delivering live, non-anomalous singletons at 230/7 to 342/7 weeks' estimated gestational age (EGA) at a single tertiary center 2016 to 2018. Patients with proteinuria assessment (24-hour total urine protein or urine protein-to-creatinine ratio extrapolation) within 3 days of SPE diagnosis were included. Patients delivered for an indication other than SPE were excluded. Patients were categorized by amount of proteinuria (mg): none (≤300), mild (301–1,000), moderate (1,001–3,000), and massive (≥3,001). The primary outcome was the proportion of potential EM time achieved (%EM), i.e., days of EM divided by days from SPE diagnosis to 34 weeks. Secondary outcomes included delivery EGA, days of EM, and perinatal outcomes. Bivariable and multivariable analyses compared outcomes across groups.Results Of 295 patients included, 21% had no proteinuria, 33% mild, 19% moderate, and 27% massive. Groups differed by EGA at diagnosis, age, parity, chronic hypertension, and renal disease. %EM was not significantly different between groups (adjusted β coefficient 4.1 [95% CI −5.3, 13.5] for mild proteinuria vs. none, −4.1 [95% CI −14.9, 6.6] for moderate proteinuria vs. none, and −5.6 [95% CI −16.0, 4.7] for massive proteinuria vs. none). Increasing proteinuria was associated with earlier delivery EGA but only days of EM in the mild versus no proteinuria groups. There was no significant association between proteinuria and maternal composite morbidity, but patients with mild and massive proteinuria had higher odds of neonatal composite morbidities compared with no proteinuria.Conclusion Among patients with SPE, proteinuria level was not consistently associated with duration of EM. However, patients with the greatest amounts of proteinuria may have worse neonatal and selected maternal outcomes.Key Points
Keywords: cesarean delivery; hypoxic ischemic encephalopathy; maternal death; intensive care unit; massive proteinuria; placental abruption; pulmonary edema